Sistemas de gestão integrados em hospitais : estudo de casos e proposição de uma estrutura de orientação para o processo de integração - Rosa, Germano Mendes (2017)
There are few hospitals with accredited and/or certified status in Brazil. However, it was observed that a small number of private hospitals has been invested in multiple certification and/or accreditation strategy, cumulating two or more certificates. This unusual condition outbursts on the hypothesis that these hospitals integrate their management systems in some degree, resulting in integrated management systems (SGI). Despite the SGI theory has been covered many manufacturing and service sectors, it is still under development stage and needs more research in healthcare field. This work has performed case studies in four hospitals which have integrated two or more management systems, seeking to identify the integration model, the integration degree, the integration strategy, and the integration maintenance mechanism used. It applied a retrospective multiple case study approach, using a semi-structured interview as main instrument to interview managers in charge of the management systems at the analysis units. All analysis units are in Minas Gerais state and were selected by convenience. The case studies indicated external stimulus as main ground to adopt multiple certification and/or accreditation strategy. As for the management systems integration process, this did not rely straightly on the models proposed by the literature, but it has emerged from the need of rule and integrate crucial disciplines in healthcare (safety, risk management, clinical pharmacy, hospital governance, etc.), which become possible through complementation of different management system standards requirements. It was not recognized any use of structured integration model, but the observed characteristics of the SGIs resembled the theoretical tecnocentric model, the integration degree just achieved the tactical and operational stratums at partial and full integrated levels, respectively. The integration strategy was characterized as mixed in three analysis units and sequential in another one. The maintenance of the SGIs has been performed by the mechanism of assimilation in all the analysis units. At the end, it presents a framework to guide the management system integration process of the standards NBR ISO 9001:2015 and NIAHO based on the model of systems.